Studi Meta-Analisis Kesediaan Penggunaan Electronic Medical Record pada Tenaga Kesehatan - Muhammad Dudayev Caesar Putra; Sarah Ayu Safitri Ekamas (Politeknik Negeri Jember, 2024)
A survey conducted by the Indonesian Hospital Association found that 50% of hospitals had implemented an electronic medical record system and only 16% had implemented electronic medical records properly. There needs to be preparation such as training, computer access, the attitude of health workers and the presence of technicians in implementing electronic medical records. This study aims to determine the relationship between training, presence of technicians, attitudes and computer access on the willingness to use electronic medical records among health workers. This research uses a systematic review and meta-analysis with dependent variables in the form of training, presence of technicians, attitudes and computer access and an independent variable in the form of willingness to use electronic medical records, which later these variables are transformed into PICO. Articles were selected using prism flow with inclusion criteria and data analysis using the Review Manager 5.3 application. A total of 12 articles met the inclusion criteria with a total sample of 5,171 health workers. The results of the meta-analysis research show that the forest plot shows that there is a relationship between training, the presence of technicians, attitudes and computer access and the willingness to use electronic medical records among health workers. Meanwhile, the funnel plot results for the presence of officers and computer access are symmetrical, while those for training and attitudes have the potential for publication bias.